The pandemic as a challenge to bioethics - Velasco Cañas, Diego Fernando (2023)
This article aims to offer a genealogical positioning of the problems that have arisen around the COVID-19 pandemic, it is examined through four moments: a) the emergence of the virus and the disease, b) the spread of the virus and declaration of the pandemic, c) control of the disease and contagion, and d) discovery of the vaccine and the post-pandemic. With this analysis we can affirm that bioethics is capable of developing a critical reflection on the need to limit the aims of predation as an objective: commercial health, relationship between human beings, environment and animal species in a natural habitat, human rights, racial discrimination, infodemic, access to resources and medical attention, "new normalities in the post-pandemic". Thus, bioethics must be projected towards a critical global and social bioethics based on systematic studies in health and life sciences that look at human behavior within moral principles.